The Causal Effect of Stop-Loss and Take-Gain Orders on the Disposition Effect - Fischbacher, Urs; Hoffmann, Gerson; Schudy, Simeon (Review of Financial Studies, 2017)
The disposition effect, i.e., the tendency to sell winning stocks too early and losing stocks too late is one of the most frequently observed and discussed biases of financial investors. We investigate in a laboratory experiment whether the option of automatic selling devices causally reduces investors’ disposition effect. Our investors can actively buy and sell assets, and, in the treatment group, additionally use stop-loss and take-gain options to automatically sell assets. Investors who had access to the automatic selling devices had significantly smaller disposition effects. The reduction was driven by a significant increase in realized losses. The proportion of winners realized was similar in both treatments. Additionally, our setup provides new evidence on which reference prices investors relate to when choosing limits for automatic sales.